Pembuatan Website Profil Sekolah Dasar Negeri 03 Kalisoro - Winoto, Pringgo; Tjendrowaseno, Tri Irianto (APMMI - Asosiasi Profesi Multimedia Indonesia, 2012)
ABSTRACT: Today many people are familiar with even use the internet in everyday life, so that in the search for community information is also often take advantage of the Internet media. Kalisoro Elementary School 03do not have the media to deliver information quickly and accurately, so far in delivery of information is still using banner of course this will take a lot of time and cost. This is one of the obstacles to improving the quality of education in public elementary school 03 Kalisoro . In this research, the website will be made regarding the profiles of public elementary school 03 Kalisoro, to promote elementary school 03 Kalisoro with an attractive appearance and can be accessed easily from anywhere via the Internet. That way elementary school 03 Kalisoro will be more known and unknown by the general public to view the profiles that are online. The method performed in the study include: literature, observation, analysis and design, website creation, implementation. Elementary School District 03 Kalisoro already have a website, so that people can find information about the 03 State Primary Schools Kalisoro online.This website is the range of information provided not only the wider community but from all corners capable of knowing Elementary School 03 Kalisoro with more complete and clear through the internet. Keywords : Website Profil ABSTRAKSI – Sekolah Dasar Negeri 03 Kalisoro belum memiliki media penyampaian informasi yang cepat dan akurat, selama ini dalam penyampaian informasinya masih menggunakan spanduk tentu saja hal ini akan menyita banyak waktu dan biaya. Hal tersebut merupakan salah satu kendala untuk meningkatkan mutu dan kualitas pendidikan di Sekolah Dasar Negeri 03 Kalisoro. Dalam penelitian ini akan dibuat website profil Sekolah Dasar Negeri 03 Kalisoro, untuk mempromosikan Sekolah Dasar Negeri 03 Kalisoro dengan tampilan yang menarik dan dapat di akses dengan mudah dari manapun melalui media internet. Dengan begitu Sekolah Dasar Negeri 03 Kalisoro akan lebih dikenal dan diketahui oleh masyarakat umum dengan melihat profil yang bersifat online tersebut. Metode yang dilakukan dalam penelitian antara lain Kepustakaan, observasi,analisis dan perancangan, pembuatan website, implementasi. Sekolah Dasar Negeri 03 Kalisoro sudah mempunyai website, sehingga masyarakat bisa mencari informasi mengenai Sekolah Dasar Negeri 03 Kalisoro secara online.dengan adanya website ini jangkauan informasi yang diberikan lebih luas bukan hanya masyarakat sekitar namun dari segala penjuru mampu mengetahui Sekolah Dasar Negeri 03 Kalisoro dengan lebih lengkap dan jelas melalui media internet. Kata Kunci : Website Profil